Strategi Pembentukan Sikap Disiplin Warga Negara Muda Melalui Persekolahan - Mariyani Mariyani; Abdul Gafur (Publikasi Pendidikan, 2018)
The formation of discipline attitude becomes the actualization of personal character on young citizens. Discipline attitude must be formed by some parties includes school. Discipline attitude is important to be formed on young citizens since some researches show that one of the indicator of successful education lies on the citizens’ discipline level. Besides, the lack of discipline is one of the causes which make someone do things against the existed moral values. Discipline attitude is an attitude which shows obedience toward the existed rules thoughtfully, with no pressure, embedded and become behavior. The aim of this research is to find out the strategy formation of young citizens’ discipline attitude through schooling. The method used in this research is library research. This research will discuss 1) discipline attitude urgency; 2) strategy formation on young citizens’ through school culture development by doing exemplary habituation, spontaneous habituation, routine and conditioning habituation; 3) strategy formation of young citizens’ attitudes through maintaining class atmosphere which is conducive and encouraging for the students. So, it will be easier for the teacher and the students collaboratively form the good class atmosphere, and; 4) strategy formation of discipline attitude through boarding school program.